Collaborative research to respond to the HIV epidemic: a case of Uganda (Makerere University)-Case Western Reserve University Research Collaboration 1988-2021 - Muzanyi, Grace; Nakibuuka, Justine; Mayanja, Harriet (African Journals Online (AJOL), 2022)
Background: Collaborative research between institutions may not yield results to transform communities. Many research collaborations come to the end of their life time without achieving their originally set goals and with a dearth of community transformation to show for it.
Objective: To delineate and highlight the achievements of the Uganda (Makerere University)-Case Western Reserve University Research Collaboration.
Methods: We retrospectively compiled and reviewed the data on research, training and policy impact achievements of the Uganda (Makerere University)-Case Western Reserve University Research Collaboration over a period of 30 years of its existence.
Results: Over the last 35 years, the Uganda (Makerere University)-Case Western Reserve University Research Collaboration trained a total of 104 Ugandans with Masters, PhDs and other varied graduate training programs. More than 70 large tuberculosis/TB+HIV studies were conducted with more than 360 manuscripts published including landmark local and global TB/HIV policy impact publications.
Conclusion: The Uganda (Makerere University)-Case Western Reserve University Research Collaboration has in the past 35 years built the capacity of Ugandan and international students through conducting landmark research, training and mentoring and contributed to TB HIV management policy changes in Uganda.
Keywords: UCWRU; collaboration; training; mentoring.